1980
DOI: 10.1254/jjp.30.199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of .ALPHA.- and .BETA.-adrenergic blockers on chlorpromazine-induced elevation of plasma glucose and cyclic AMP in fed mice.

Abstract: Abstract-The subcutaneous administration of chlorpromazine (CPZ) caused a dose response increase in plasma glucose and cyclic AMP levels in fed male mice. Hex amethonium abolished the elevation of both plasma glucose and cyclic AMP. Pro pranolol did not inhibit the elevation of plasma glucose but inhibited the increase of plasma cyclic AMP. In contrast, phentolamine and yohimbine completely suppressed the elevation of plasma glucose but not that of plasma cyclic AMP. These results indicate that the hyperglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The release of medullary epinephrine is controlled by sympathetic preganglionic (cholinergic) neurons and thus could be blocked by the ganglionic blocker hexamethonium. Our finding that pretreatment with hexamethonium completely inhibited the elevation of plasma glucose induced by either chlorpromazine or clozapine confirms and extends earlier data on the effects of combined chlorpromazine and hexamethonium administration in mice 12 and rats. 23 In the present studies, chlorpromazine-and clozapine-induced hyperglycemia in mice was also completely blocked by pretreatment with the a 2 adrenoceptor antagonist, yohimbine, suggesting that the hyperglycemic effect is due to increased sympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The release of medullary epinephrine is controlled by sympathetic preganglionic (cholinergic) neurons and thus could be blocked by the ganglionic blocker hexamethonium. Our finding that pretreatment with hexamethonium completely inhibited the elevation of plasma glucose induced by either chlorpromazine or clozapine confirms and extends earlier data on the effects of combined chlorpromazine and hexamethonium administration in mice 12 and rats. 23 In the present studies, chlorpromazine-and clozapine-induced hyperglycemia in mice was also completely blocked by pretreatment with the a 2 adrenoceptor antagonist, yohimbine, suggesting that the hyperglycemic effect is due to increased sympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 91%
“…Acute hyperglycemic effects of antipsychotics have been demonstrated in preclinical animal models for chlorpromazine in mice 11,12 and rats 13 and for various atypical antipsychotics in mice. 14 In addition, a recent hyperinsulinemic, euglycemic clamp study in rats showed the rapid development of peripheral insulin resistance after acute clozapine and olanzapine administration.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that CPZ causes hyperglycemia and an increase in plasma cyclic AMP level in mice through stimulation of the sympathetic nervous system (2-4). CPZ-induced hyperglycemia and in creases in plasma cyclic AMP level were completely abolished by the treatment of mice with adrenalectomy or hexamethonium bromide, a ganglion blocker (2)(3)(4). This indicates that there is no possibility that CPZ can raise the plasma glucose and cyclic AMP level by decreasing the phosphodiesterase activity in the peripheral tissues or blood due to calmodulin antagonistic action.…”
Section: Chlorpromazinementioning
confidence: 96%
“…According to this effect, the higher doses of methanolic extract of P. yohimbe bark (40 and 80 mg/kg/mL) may facilitate glucagon secretion and thus lesser reduction in blood glucose level was obtained. It was reported that, yohimbine may cause gradual increases in glucagon secretion [28][29][30][31].…”
Section: Open Accessmentioning
confidence: 99%